THE CRIME OF BODILY HARM AND THE IMPLICATIONS THEREOF IN THE MENTAL AND EMOTIONAL INTEGRITY OF THE VICTIM - Buneci, Bogdan; Codescu, Cătălin (International Journal of Legal and Social Order, 2026)
The traumatic injuries suffered by victims of bodily harm offences are analysed, from a legal perspective, as a component of the constitutive elements of the offence, namely the immediate consequence. These injuries overlap with the consequences expressly provided for in the criminalisation text, specifically Article 194(1) of the Criminal Code. Thus, the assessment focuses on the extent to which the victim’s physical (bodily) integrity has been affected, for the purpose of determining the correct legal classification of the act committed. This allows for an analysis of how the victim's physical (bodily) integrity is affected, for the purpose of legally classifying the specific act committed. How is mental integrity affected by physical trauma assessed from a legal perspective? It is unanimously accepted in the legal doctrine It is unanimously accepted in the legal sphere and regulated by constitutional and branch rules that there is a symbiosis between the physical and mental integrity of the human being. Regarding the close and inseparable link between the two types of integrity, in light of the provisions of Article 3 of the Charter of Fundamental Rights of the European Union, the renowned professor and researcher at the European Academy of Bolzano, Gabriel N. Toggenburg, stated that "human beings are like ancient amphorae. Each one is unique. Each must be treated with care. Violence leaves permanent marks and causes irreparable damage. The internal and external dimensions of an amphora cannot be isolated from each other. This is why Article 3 of the Charter of Fundamental Rights of the European Union protects not only the physical but also the 'mental integrity' of all human beings."[1] The analysis of the trauma suffered by the victim, both physically and especially psychologically and emotionally, must be carried out in order to establish the damage, using civil law rules and not criminal law rules. The choice of specific criteria for assessing how mental and emotional integrity has been affected, and the means of evidence that can support the existence, severity and duration of the damage to the victim's psycho-emotional balance, is key to the fair resolution of this type of criminal case. [1] Gabriel N. Toggenburg, The3rdof all EU rights: Integrity and how the Charter contributes/The European Academy of Bozen/Bolzano (EURAC) - https://www.eurac.edu/en/blogs/eureka/the-3rd-of-all-eu-r-rights-integrity-and-how-the-charter-contributes